Business Model Canvas pada Bisnis Bawang Merah Goreng “SUPERBRAM” di KWT Putri Manunggal Kabupaten Kulonprogo - Fatkhiyah Rohmah; Anggun Pramudita; Aulia Putri Nur Cahyani; Azka Aulia Qayyum; Muhammad Dhafa Putra Bahagia; Rahmatia Destriani; Agus Dwi Nugroho (AGRIFITIA : Journal of Agribusiness Plantation, 2026)
Micro-enterprises in the agribusiness sector play a vital role in supporting local economies and empowering communities, particularly through product innovation based on regional potential. One such example is the Superbram fried shallot business managed by the Women Farmers Group (KWT) Putri Manunggal in Kulon Progo Regency. This study aims to analyse the business model of the Superbram fried shallot enterprise managed by KWT Putri Manunggal, using the Business Model Canvas (BMC) approach, which comprises nine key components. The analysis is complemented with a SWOT approach to identify the strengths, weaknesses, opportunities, and threats within each BMC element. The findings indicate that Superbram possesses strengths in product quality and support from strategic partners, but still faces challenges in production capacity, packaging innovation, digital promotion, and revenue diversification. The SWOT analysis recommends strategies such as strengthening long-term partnerships, adopting appropriate technology, developing products and packaging, and optimizing digital marketing. These findings provide a foundation for formulating more adaptive and sustainable business development strategies to address market dynamics and competition among micro, small, and medium enterprises (MSMEs) in the agribusiness sector. Keywords: SWOT; agribusiness; small enterprise; fried shallots; development strategy     ABSTRAK Usaha mikro di sektor agribisnis memiliki peran penting dalam mendukung ekonomi lokal dan pemberdayaan masyarakat, terutama melalui inovasi produk berbasis potensi daerah. Salah satu contohnya adalah usaha olahan bawang merah goreng Superbram yang dikelola oleh KWT Putri Manunggal di Kabupaten Kulon Progo. Penelitian ini bertujuan untuk menganalisis model bisnis usaha bawang merah goreng Superbram di KWT Putri Manunggal, menggunakan pendekatan Business Model Canvas (BMC) yang terdiri dari sembilan elemen utama. Analisis dilengkapi dengan pendekatan SWOT untuk mengidentifikasi kekuatan, kelemahan, peluang, dan ancaman pada masing-masing elemen BMC. Hasil penelitian menunjukkan bahwa usaha Superbram memiliki keunggulan dalam kualitas produk dan dukungan mitra strategis, namun masih menghadapi tantangan dalam hal kapasitas produksi, inovasi kemasan, promosi digital, serta diversifikasi pendapatan. Analisis SWOT merekomendasikan strategi penguatan kemitraan jangka panjang, adopsi teknologi tepat guna, pengembangan produk dan kemasan, serta optimalisasi pemasaran digital. Temuan ini memberikan dasar bagi penyusunan strategi pengembangan usaha yang lebih adaptif dan berkelanjutan dalam menghadapi dinamika pasar dan persaingan usaha mikro, kecil, dan menengah (UMKM) di sektor agribisnis. Kata Kunci: SWOT; agribisnis; usaha kecil; bawang merah goreng; strategi pengembangan